2020
DOI: 10.3389/fnsyn.2020.575863
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Through Nitric Oxide Synthase Promotes the Formation of Multi-Innervated Spines

Abstract: Structural plasticity of synapses correlates with changes in synaptic strength. Dynamic modifications in dendritic spine number and size are crucial for long-term potentiation (LTP), the cellular correlate of learning and memory. Recent studies have suggested the generation of multi-innervated spines (MIS), in the form of several excitatory presynaptic inputs onto one spine, are crucial for hippocampal memory storage. However, little is known about the molecular mechanisms underlying MIS formation and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Although these changes also occur during normal aging, as reported in other aged species [26,27], in the 3xTg-AD mice, the downregulation of these Wnt components occurred earlier than in the control mice and was particularly severe. In addition to the negative effects of Dkk-1 and the decrease in the agonist Wnt7a, we found that the symptomatic stage of pathology in transgenic mice could worsen synaptic function because of its role in promoting synaptic plasticity events [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Although these changes also occur during normal aging, as reported in other aged species [26,27], in the 3xTg-AD mice, the downregulation of these Wnt components occurred earlier than in the control mice and was particularly severe. In addition to the negative effects of Dkk-1 and the decrease in the agonist Wnt7a, we found that the symptomatic stage of pathology in transgenic mice could worsen synaptic function because of its role in promoting synaptic plasticity events [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight another microanatomical specialization concerning the presence of single AS on spines, although its functional relevance remains unclear. In fact, the generation of multi-synaptic spines has been associated with synaptic potentiation, and has been linked to memory processes (Giese et al, 2015; McLeod et al, 2020). Furthermore, in the mouse neocortex, it has been suggested that spines receiving one AS and one SS are electrically more stable than spines establishing a single AS (Villa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of having single or multiple synapses on the same spine is yet to be fully understood. The formation of multi-synaptic spines has been linked to synaptic potentiation and memory processes (Giese et al, 2015; McLeod et al, 2020). In the mouse neocortex, it has been suggested that spines receiving one AS and one SS are electrically more stable than spines with a single AS (Villa et al, 2016).…”
Section: Common Synaptic Characteristicsmentioning
confidence: 99%